Face Recognition Based on Features of Triple Descriptors - Elkarami, Bashier; Ahmadi, Majid (International Journal of Engineering and Technology, 2018)
Recently, texture descriptors and object detection descriptors have been used widely in face recognition due to their discriminative ability and fast implementation. In this paper, we investigate the efficiency of face recognition based on image blocking and a combination of triple descriptors, LBP, LTP, and HOG.Â The method is applied to Color Feret dataset and AT&T along with four classifiers to measure the accuracy rate. The experimental results show a better recognition rate on AT&T and stable performance on both datasets. Â Â